Ability of a confocal scanning laser ophthalmoscope (TopSS) to detect early glaucomatous visual field defect. Issue 8 (1st August 2000) - Ahn, Byoung-Sun; Kee, Changwon
Abstract : AIMS: To evaluate the ability of the confocal scanning laser ophthalmoscope (TopSS) to detect early glaucomatous visual field defect using our unique discriminant criteria. METHODS: The optic discs of 110 eyes of normal Korean subjects were examined and normal values for each variable were obtained according to the size of the optic disc. The five most sensitive optic disc variables for discriminating glaucoma were then applied to one eye of 80 Korean subjects with primary open angle glaucoma or normal tension glaucoma. Only eyes with an optic disc size of 2.0–3.0 mm 2 and a contour tilt of less than 3° were included. These variables were used to develop unique discriminant criteria for detecting early glaucomatous visual field defect and their sensitivity and specificity were calculated in three groups of patients with visual field loss. RESULTS: The five most sensitive variables were half the depth area, cup/disc (C/D) ratio, total area of the neuroretinal rim (NRR), volume above, and localised thinning of the NRR. The following criteria were used to diagnose glaucoma: (1) total area of the NRR decreased and one of the other four variables abnormal, and (2) total area of the NRR normal, localised thinning of the NRR, and one of the other three variables abnormal. The sensitivity of these criteria was 89.7% in patients with a mildly impaired visual field and 100% in those with a moderately or severely impaired visual field; the specificity was 89.1%. CONCLUSIONS: The discriminant criteria used had high sensitivity and specificity in the diagnosis of glaucoma and the TopSS can be useful in the early detection of changes in the glaucomatous optic disc.